On the Periphery or at the Centre?: Ideas for Improving the Physical and Interpersonal Environments for Lesbian, Gay, Bi-sexual, and Trans-sexual/gender Students at a New Zealand Secondary School. - Wendy Hemi; Anita Mortlock (New Zealand Journal of Teachers' Work)
Despite mandates that require schools to be safe places for all students, issues persist around the provision of safety for lesbian, gay, bi-sexual, trans-sexual, and trans-gendered students and staff. The current study reports the initial two stages of an action research project undertaken in a New Zealand secondary school, which aimed to enhance the interpersonal and physical environments for students with diverse gender identities and sexual orientations. The first phase consisted of data gathering, comprising an evaluation of the physical environment and a survey issued to students and staff. The second phase was the development of a plan for ongoing action and improvement, consisting of education, provision of safe spaces and meaningful support, and artefacts that communicate tolerance.